Clinical Laboratory Changes in Children with Hematuric Form of Chronic Glomerulonephritis Following Chronic Epstein - Barr Virus Infection - Ye.N. Tolchennikova (Zaslavsky O.Yu., 2012)
The purpose is to study the clinical laboratory features of hematuric form of chronic glomerulonephritis (HFCGN) in children with chronic Epstein - Barr virus infection (EBVI). 110 children with HFCGN at the age of 3-17 years were examined. For EBVI detection IgM, IgG EA, IgG VCA, IgG EBNA were determined by method of immune-enzyme analysis, viral antigen - by method of polymerase chain reaction in blood, saliva, urine. Chronic EBVI was detected in 54 (49.1 %) of children with HFCGN. Mean age of HFCGN onset in group of children with EBVI was 5.57 ± 0.50 years against 8.02 ± 0.46 years in children without EBVI. Common clinical features in patients with chronic EBVI were higher frequency of significant erythrocyturia, presence of macrohematuria and tubular disorders, systemic lymphadenopathy, hepatosplenomegaly, asthenic syndrome, leukopenia, lymphocytosis, monocytosis. The severity of erythrocyturia and presence of tubular disorders depended on the degree of EBVI activity.